National Context, Religiosity, and Volunteering: Results from 53 Countries - Ruiter, Stijn; De Graaf, Nan Dirk (American Sociological Review, 2006)
To what extent does the national religious context affect volunteering? Does a religious environment affect the relation between religiosity and volunteering? To answer these questions, this study specifies individual level, contextual level, and cross-level interaction hypotheses. The authors test the hypotheses by simultaneously studying the impact of religiosity of individuals, the national religious context, and their interplay on volunteering while controlling for possible confounding factors both at individual and contextual levels. Based on multilevel analyses on data from 53 countries, frequent churchgoers are more active in volunteer work and a devout national context has an additional positive effect. However, the difference between secular and religious people is substantially smaller in devout countries than in secular countries. Church attendance is hardly relevant for volunteering in devout countries. Furthermore, religious volunteering has a strong spillover effect, implying that religious citizens also volunteer more for secular organizations. This spillover effect is stronger for Catholics than for Protestants, non-Christians and nonreligious individuals.